Application of Sociodrama Techniques Based on Tabe Culture to Improve Polite Character - Sukiman, Nurfajriyanti; Latif, Suciani; Zulfikri, Zulfikri (IAIN Kudus, 2026)
Application of Sociodrama Techniques Based on Tabe Culture to Improve Polite Character. This study aims to describe the character of students' politeness, the implementation of group guidance services with sociodrama techniques based on tabe culture , and the effect of its application on improving politeness. Tabe culture is a form of politeness typical of the Bugis-Makassar community which is manifested through the expression